Prospects for Creating Bearing Details Using Secondary Materials - Gulyam, Urishev; o`g`li, Mo`minov Shukurillo Maribjon (International Journal on Orange Technologies, 2023)
This article talks about the future prospects of the production of bearings from secondary metal waste and their use in machine building, aviation, and shipbuilding. Bearings made of secondary metals are economically more convenient and have a significant positive impact on the environment.